Kinematic and Dynamic Modelling of a 6-DOF Robotic Manipulator for Industrial Applications - Anushka Mukherjee (International Journal of Robotics and Automation in Mechanics, 2025)
The rapid evolution of industrial automation has intensified the need for highly accurate, flexible, and intelligent robotic systems capable of operating in dynamic and demanding environments. Among these systems, six-degree-of-freedom (6-DOF) robotic manipulators have emerged as a versatile solution due to their superior dexterity, large workspace, and human-arm-like motion capabilities. This research focuses on the comprehensive kinematic and dynamic modelling of a 6-DOF robotic manipulator designed for various industrial tasks such as material handling, welding, assembly, and inspection. The study employs the Denavit-Hartenberg (D-H) convention to derive both forward and inverse kinematic equations that establish the spatial relationship between joint parameters and the end-effector pose. The forward kinematics determine the position and orientation of the end-effector with respect to the base frame, while the inverse kinematics provide joint configurations required to achieve desired trajectories. For dynamic analysis, the Euler-Lagrange formulation is utilized to obtain a detailed model incorporating the effects of inertia, Coriolis, centrifugal, and gravitational forces. The resulting equations describe the complete motion behaviour of the manipulator and form the basis for controller design, trajectory planning, and optimization. Simulation studies validate the developed model, demonstrating smooth trajectory tracking, stable torque distribution, and reliable performance under varying payloads. The results highlight how accurate mathematical modelling directly enhances control precision, operational safety, and energy efficiency in automated manufacturing processes. Overall, the integration of kinematic and dynamic models presented in this work provides a foundational framework for future advancements in intelligent control, adaptive systems, and human-robot collaboration within modern industrial automation.
Keywords: 6-DOF manipulator; Automation; Denavit-Hartenberg parameters; Euler-Lagrange dynamics; industrial robotics; motion control